2004
DOI: 10.1016/j.ymthe.2004.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Lowering of Plasma Cholesterol Levels in LDL-Receptor-Deficient WHHL Rabbits by Gene Therapy

Abstract: Lentiviral vectors encoding rabbit low-density lipoprotein receptor (LDLR) or green fluorescent protein (GFP) under the control of a liver-specific promoter (LSP) were used for intraportal gene transfer into the liver of hypercholesterolemic LDLR-deficient Watanabe Heritable Hyperlipidemic rabbits. In vitro cell culture analysis demonstrated functionality of the LSP-LDLR vector in mediating increased degradation of LDL in transduced liver cells. Twenty-five rabbits were each injected with 1 x 10(9) infectious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…1,8,23 The most frequently used hepatocyte-specific promoters, with or without fusion of one or two heterologous enhancer elements, are the human AT promoter, 4,12,26,27 the albumin promoter 28,29 and the LSP promoter. 3,7,9 In this direct comparative study using hydrodynamic and adenoviral gene transfer, we show that the DC172 promoter, consisting of a 890 bp human AT promoter and two copies of the 160 bp a 1 -microglobulin enhancer, combined with two or four copies of the HCR-1 3 0 of the transgene, constitutes the most potent expression cassette. The a 1 -microglobulin/bikunin precursor promoter is weak and ubiquitously active, but expression in PC is potently increased by a hepatocytespecific enhancer located 2.7 kb downstream of the promoter.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…1,8,23 The most frequently used hepatocyte-specific promoters, with or without fusion of one or two heterologous enhancer elements, are the human AT promoter, 4,12,26,27 the albumin promoter 28,29 and the LSP promoter. 3,7,9 In this direct comparative study using hydrodynamic and adenoviral gene transfer, we show that the DC172 promoter, consisting of a 890 bp human AT promoter and two copies of the 160 bp a 1 -microglobulin enhancer, combined with two or four copies of the HCR-1 3 0 of the transgene, constitutes the most potent expression cassette. The a 1 -microglobulin/bikunin precursor promoter is weak and ubiquitously active, but expression in PC is potently increased by a hepatocytespecific enhancer located 2.7 kb downstream of the promoter.…”
Section: Discussionmentioning
confidence: 86%
“…Transcriptional targeting by use of hepatocyte-specific expression cassettes may lead to immunological ignorance or tolerance for the transgene product. [1][2][3] Expression cassettes for hepatocyte-directed transfer have been improved by using new promoterenhancer combinations, [3][4][5][6][7][8][9] inclusion of introns 5,[10][11][12][13] and inclusion of additional transcriptional sequences like scaffold matrix-attached regions (SMAR) and hepatic control regions (HCR). 12,[14][15][16][17][18] However, because different gene transfer vectors, different doses and different transgenes were used in these studies, direct comparative data for different expression cassettes are often lacking and hamper the interpretation of existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this reasons it is a vector in which the interest has decreased. Recently, lentivirus have been used mainly to transfer genetic material to cells of the vascular wall, they have demonstrated a high efficiency of infection in smooth muscle and elicit a minimum immune response, nevertheless, the tropism for myocardium is limited and its production in great amounts is difficult, thus currently is not a viable option and requires engineering of this vector to improve its utility on a large scale, facilitating its production (Kankkonen et al, 2004). Sendaivirus and herpesvirus, have been mentioned as possible useful vectors, but sufficient data to this date does not exist on their utility (Masaki et al, 2001).…”
Section: Vectors Used For Cardiovascular Gene Therapymentioning
confidence: 99%
“…FH is caused by mutations in the LDL receptor which binds and internalises LDL cholesterol in response to low intracellular cholesterol levels. Gene therapy for FH been under investigation for a number of years with many published investigations reporting lowering of plasma cholesterol following delivery of cDNA vectors where expression is driven by heterologous promoters and delivery is achieved by virus-mediated liver-directed transduction with retrovirus (Miyanohara et al 1988;Wilson et al 1988;Chowdhury et al 1991;Grossman et al 1995;Kankkonen et al 2004), adenovirus (Ishibashi et al 1993;Kozarsky et al 1994;Li et al 1995;Kozarsky et al 1996;Nomura et al 2004;Jacobs et al 2008;Van Craeyveld et al 2011) and adeno-associated virus (Lebherz et al 2004;Kassim et al 2010). These previous studies included a clinical trial (Grossman, Rader et al 1995) that showed no evidence of long-term therapeutic effect.…”
Section: Physiologically-relevant Gene Expression Vectors: Use Of Natmentioning
confidence: 99%